From the CONSORT to the ConPhyMP statement and beyond—how to ascertain best practice - Heinrich, Michael; Jalil, Banaz (Frontiers in Pharmacology, 2023)
With the implementation of the ConPhyMP reporting tool as an element of peer review in Frontiers in Pharmacology, Section Ethnopharmacology and in other journals, this short perspective papers highlights the use of a new tool available via the website of the Society for Medicinal Plant and Natural Product Research (https://ga-online.org/best-practice/) and how to use it. The guidelines and the tool cover the relevant aspects which need to be reported when studying a plant extract using pharmacological, toxicological microbiological, clinical and other approaches. In our vision, science will only remain impactful if it is based on a drive for best practice, i.e. on a sound conceptual and methodological basis.